The mesocortical dopamine projection to anterior cingulate cortex plays no role in guiding effort-related decisions. - Walton, M; Croxson, P; Rushworth, M; Bannerman, D (2005)
Both mesolimbic dopamine (DA) and the anterior cingulate cortex (ACC) have been implicated in enabling animals to expend effort to obtain greater reward. To investigate the role of the DA pathway to ACC in working for reward, the authors tested rats on a cost-benefit T-maze paradigm in which they could either climb a barrier to obtain large reward in 1 arm (high reward [HR]) or select the low-effort alternative containing less reward (low reward [LR]). Surprisingly, ACC DA depletions had no effect on choice performance. Manipulations of barrier and reward sizes demonstrated that lesioned rats were as sensitive to the costs and benefits of the alternatives as controls. These results imply that the DA projection to ACC is not involved in guiding effort-related decisions.